Price or pride? Malaysian marine cruising behaviour - Chong, Daniel Ka Leong * (Taylor & Francis, 2018)
Despite substantial investments and promotional efforts in developing cruise tourism in Asia, cruise liner managers and marketers are given little indication concerning the effectiveness of their current marketing programs in driving consumer intentional behaviour. This study of a cruise liners’ marketing program validates the position of emotional value, social value and perceived novelty on the consumers’ intention to cruise. While marketing programs for cruise vacation in their current form do offer some brand building benefits, their effect on cruising intention is significantly stronger for younger customers who are inclined to brand as a self-reflection. In contrast, the price has no direct effect on intention to cruise. Therefore, this cruise marketing program does provide some value, but conceivably not in the way the cruise liner company wishes. The cruise industry should anticipate their customers’ perpetual characteristics (i.e. their interpretation of luxury vacation and perceived importance of social status reflection through choice of vacation) and review these marketing approaches to ensure that they able to reach out to their customers better rather than just attracting price sensitive customers.